A Comparative Study on Zakat Management Law Practices between Malaysia and Indonesia - Irma Rachmawati Ma’ruf; Ali Anwar Jusuf; Ram Al Jufri; Juniardi Swastria; Dhani Supriadi; Ponirah Kartika Rahayu; Aang Arifin (International Journal of Science and Society, 2020)
Zakat management, that is collection and distribution funds, is an important to economy and society, in countries like Indonesia, Malaysia. They are controlled by government, which dictates the administration and management of zakat institutions. One of the issues is the level of zakat distribution is lower than the zakat collection. Hence, there are surplus of millions of zakat funds that are not distributed to the recipients. The purpose of this study is to identify the factors that lead to zakat as a productive asset and increase, and to explore and examine the management of zakat institutions in Malaysia, Indonesia and Singapore. The methodology used is a qualitative analytical description which analyze key provision of relevant law impacted upon the law of management zakat in Indonesia, Malaysia, and Singapore. The research is conducted by comparative approach. Based on the results of this study, the law of management zakat in Malaysia is better, however the management of zakat in Indonesia is better in distributions.